Pilot study on integrating YanZhao cultural elements into wayfinding signage at Hebei Garden Expo Park - Zhuxiao, Fan; Ibrahim, Nur Hisham; Sulaiman, Shahrunizam (Universiti Teknologi MARA, Perak, 2025)
This study evaluates the feasibility of integrating YanZhao cultural elements into Wayfinding signage at Hebei Garden Expo Park. Through a pilot study, initial feedback from visitors was collected to assess the effectiveness and appeal of culturally integrated signage. The findings from this pilot study were used to refine the interview questions and research methodology for the main study. This research aims to enhance visitor experience, promote regional culture, and improve navigation efficiency by incorporating YanZhao cultural elements into Wayfinding signage.